HER-2/neu overexpression in breast cancer - Aziz, Rana S.; Rasheed, Nabeel W. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: In breast carcinoma, amplification &/or over-expression of HER-2/neu has been associated with a group of unfavorable prognostic factors. The Food & Drug Administration Agency approved Trastuzumab (Herceptin) for the therapy of metastatic breast cancer but only in patients with amplification &/or over-expression of this gene. Because of these advances, evaluation of HER-2/neu status in breast cancer specimens is of vital importance. Patients and methods: thirty eight females with breast carcinoma were included in this study. All histologic sections were stained routinely with the hematoxylin and eosin stains and immunohistochemically for HER2/neu. All cancers were graded and subcategorized into ductal and lobular carcinomas, with or without an insitu component, and with or without Paget disease. The assessment of HER-2/neu over-expression was quantitated. Results: Of the twenty four cases of infiltrative duct carcinoma (IDC), HER-2/neu staining was positive in ten (41.7%) cases. None of the fourteen cases of infiltrative lobular carcinoma (ILC) showed a positive reaction. Statistical analysis revealed no significant differences in respect to HER2/neu expression between IDC with and without ductal carcinoma in situ (DCI). All cases of IDC with overlying Paget disease (5 cases; 13.2%) were positive for the stain. All grade I cancers were negative for HER-2/neu over-expression, in contradistinction to a positive staining in 41.7% grade II tumors and 62.5% grade III tumors. Conclusion: there is significant correlation between HER2/neu overexpression and cancer histopathological type. The presence or absence of an in situ component had no effect on the marker overexpression. Significant correlation was observed between HER-2/neu overexpression and higher histological grades of IDC. No correlation was found between the positivity of the marker and axillary lymph node status. Similarly, no association was found with the other variables except the size of tumor. It is recommended that HER-2/neu assessment to be included as a routine test in the screening program of all breast cancer Iraqi patients.